Association between oxidative DNA damage, fruits and vegetables intake with breast cancer: a preliminary study in Klang Valley - Suzana Shahar,; Kim, Tiu Teng; Nor Fadilah Rajab,; Fatimah Arshad, (Penerbit UKM, 2008)
A preliminary study was conducted to determine the level of oxidative DNA damage, fruits and vegetables intake among 50 breast cancer patients (cases) as compared to 50 healthy women (controls) with no known medical history of breast cancer in Klang Valley. Both groups were matched for age and ethnicity. Data on socio-demographic, health status and medical history, fruits and vegetables intake, and supplements intake were obtained through an interviewbased questionnaire. Anthropometry measurements included weight, height, and waist and hip circumference were also carried out on subjects. A total of 3mL fasting venous blood was drawn to assess lymphocytes oxidative DNA damage using Alkaline Comet Assay. Results indicated that the mean intake of fruits and vegetables was lower in cases (4.09 ± 1.17 servings/d) than controls (4.77 ± 0.90 servings/d)(p < 0.05) The intake of fruits and vegetables from family groups of solanaceae, myrtaceae, caricaceae, apiaceae, brinjal, rutaceae, broccoli, orange, carrot, watermelon were 0.5 - 1 servings/week significantly higher among controls as compared to cases (p < 0.05 for all parameters). However, the intake of fruits from rosaceae family and apple was higher among controls than cases (p < 0.05). The estimated intake of β-carotene, carotenoids, vitamin A, vitamin C (p < 0.001), α-carotene and lycopene (p < 0.05) from fruits and vegetables were higher among controls than cases. Mean DNA damage level of cases (4.55 ± 1.78 % DNA in tail, %TD; 0.35 ± 0.21 tail moment, TM) were 3.5 and 3.9 times higher than the value of controls (1.3 ± 0.70% TD; 0.09 ± 0.09 TM) (p < 0.001) and the damage increased with higher values of waist hip ratio (% TD, r = 0.396, p < 0.05; TM, r = 0.349, p < 0.05) and waist circumference (% TD, r = 0.334, p < 0.05; TM, r = 0.360, p < 0.05). There was an inverse relationship between oxidative DNA damage with intake of total fruits and vegetables, cauliflowers and water convolvulus and also consumption from rutaceae and solanaceae families. Similar trend was noted for estimated Jurnal Sains Kesihatan Malaysia 6 (1) 2008: 61-7762 intake of vitamin A, carotenoids, vitamin C, β-carotene and lycopene. In conclusion, the intake of fruits and vegetables of five servings/d and the consumption of specific families and types of fruits and vegetables might protect against oxidative DNA damage and further reduce breast cancer risk.